Abstrak : Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui Peran Layanan Konseling Individu Psikoanalisis Dalam Mengatasi Tindakan Kleptomania Siswa Kelas XI SMK N Matesih Tahun Pelajaran 2021/2022.Penelitian ini dilaksanakan di SMK - Rachmawati, Rizky (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Abstrac : This study aimed to see the role of the psychoanalytic individual counseling in overcoming students’ kleptomaniac behaviors in Class XI SMKN Matesih in the 2021/2022 academic year. To this end, A 3-cycle guidance and counseling action research was applied. Each cycle consisted of four stages: planning, action, observation, and reflection. The data were collected using interviews, observation, documentation, and Who am I psychological test. The collected data were analyzed using a qualitative descriptive technique with the technique triangulation. Three students were identified to exhibit mild kleptomaniac disorders, commonly known as hypomania. The following percentage of kleptomaniac behavioral characteristics were obtained in each cycle: Precycle: 46%, cycle I: 44.6%, cycle II: 33.32%, cycle III: 22.8%, and cycle IV: 14.72%. This result shows that psychoanalytic individual counseling is effective in treating individuals with mild kleptomaniac symptoms, allowing them to control the urge to steal. Keywords : Individual counseling, psychoanalysis, Kleptomania